A carbon nanocoil-based flexible tip for a live cell study of mechanotransduction and electro-physiological characteristics. Issue 7 (23rd January 2020) - Wang, Peng; Geng, Chunyang; Pan, Lujun; Liu, Bo
Abstract : An individual CNC tip is used to apply local mechanical and electrical stimulation on a single live cell, and it shows excellent biocompatibility and physical properties for the study of signal transduction non-invasively in live cells. Abstract : The responses of living cells to external mechanical and electrical stimulation play important roles in regulating their biological functions and behaviors, and the response mechanisms have attracted great attention. Global stimulation on cells is generally used in traditional methods, but it is insufficient to investigate the mechanism of a dynamic physiological response at the subcellular level. At present, there is still lack of a low-cost and easy-operated method to apply local mechanical force and electrical stimulation on living cells. In this study, an individual carbon nanocoil (CNC) is used as a microscale noninvasive tool for local stimulation on a single cell, and a living cell imaging technology, fluorescence resonance energy transfer (FRET), is adopted to determine the responses of cells. After demonstrating that CNCs have low cytotoxicity to be applied in the biological field, an individual CNC is used as a needle tip to apply local mechanical force on a single osteosarcoma cell, which is transfected with a Src FRET biosensor to explore the mechano-physiological response. A spatially increasing and polarized Src protein activation is observed on the stimulated cell. Moreover, a single CNC is also used as an electrode to exert periodic local electrical stimulation. Osteosarcoma cells transfected with calcium-FRET biosensors show notable spatial-polarized FRET emission ratio distribution, and the FRET ratio shows a recoverable tendency towards the initial state after withdrawing the electrical stimulation. The cell biofunctions and structures are not damaged during the experiment process, which indicates that CNC is a kind of non-invasive and bio-safe tip. The CNC tip is a powerful tool for exploring the mechanotransduction and electro-physiological characteristics of living cells.